Effect of Pleurotus eryngii Mushroom β‐Glucan on Quality Characteristics of Common Wheat Pasta. Issue 4 (25th February 2016) - Kim, SunHee; Lee, Jo‐Won; Heo, Yena; Moon, BoKyung
Abstract: The objective of this study was to evaluate the effect of β‐glucan‐rich fractions (BGRFs) from Pleurotus eryngii mushroom powder on the quality, textural properties, and sensory evaluation of common wheat pasta. Pasta was prepared from semolina flour and common wheat flour by replacing common wheat flour at 2%, 4%, and 6% with BGRFs. Semolina flour showed significantly higher viscosities than common wheat flour samples. However, all viscosities, except the breakdown viscosity, were reduced with increasing percentages of BGRFs. Replacement of the common wheat flour with BGRFs resulted in a reddish brown colored pasta with a lower L * value and a higher a * value. The common wheat pastas containing up to 4% BGRFs were not significantly different from semolina pasta with regard to cooking loss. Addition of up to 2% BGRFs had no significant impact on swelling index and water absorption. The addition of BGRFs in common wheat flour had a positive effect on the quality of common wheat pasta and resulted in hardness values similar to those of semolina pasta. In a sensory evaluation, cooked pasta with 2% BGRFs had the highest overall acceptability score. In summary, the results showed that common wheat flour containing 4% BGRFs could be used to produce pasta with an improved quality and texture properties similar to semolina pasta.